MAGNETIC RESONANCE TOMOGRAPHY IN SLEEP APNEA SYNDROME DIAGNOSTICS - M. A. Shariya; E. A. Butorova; A. Yu. Litvin; D. V. Ustyuzhanin; Е. М. Elfimova; Sh. B. Gorieva; S. K. Ternovoy; I. E. Chazova (Кардиоваскулярная терапия и профилактика, 2015)
Aim. To study the specifics of soft tissues surrounding upper airways (STSUA) structure using magnetic resonance tomography (MRI) in patients with obesity and obstructive sleep apnea syndrome (OSAS). Material and methods. Totally 40 men studied with the mean age 44,7±9,6 y. Of those 20 had obesity of I-II grade — with body mass index (BMI) 35,1±3,4 кг/м2 and severe OSAS (apnea-hypopnea index — AHI — was 53,4±15,7). Controls consisted of 20 persons without obesity — BMI 23,8±1,3 kg/m2 . Assessment of upper airways was performed on Philips Achieva 3.0T tomograph. We measured the volumes of soft palate (VSP), tongue (VT), lateral pharyngeal walls (VLPW) and the squares of maximum upper airways narrowing (SMUAN) at retropharyngeal (RP) and retroglossal (RG) levels. Results. In obese patients with OSAS we found higher values of TV — 70,5±12,4 vs 45,0±5,7 cm3 , VSP — 7,5±1,7 vs 3,5±0,7 cm3 , VLPW at the level of RP — 11,7±4,1 vs 3,2±0,8 cm3 , VLPW at the level of RG — 10,4±2,8vs 3,1±8,4 cm3 and lower values of SMUAN at the level of RP — 6,3±3,5 vs 14,0±3,8 cm2 , as RG — 19,3±7,5 vs 27,0±5,0 mm2 . All differences were statistically significant (p<0,001). Conclusion. MRI can be successfully applied for the evaluation of STSUA parameters of upper airways openness.